PENGUATAN AKSES INTERNET KEPADA MASYARAKAT DI DESA TEMPURAN KECAMATAN KALORAN KABUPATEN TEMANGGUNG - Muhammad Baidlowi; Maskatim; Alim Bimo Pratowo; Raihan Afif Edisyah (JURNAL NAGARA BHAKTI, 2023)
The composition of the population of Tempuran Village, Kaloran District, Temanggung Regency consists of students, private employees and farmers. For people in the digital age, of course, the use of the internet will be very useful and become a necessity, to support daily activities that are required to use the internet. The limited condition of the internet network is one of the factors causing obstacles in community activities and has an impact on the results and quality of education and lack of information and the loss of opportunities to enjoy various facilities in the use of the internet. Defense Electrical Engineering Study Program Akmil, with all the power and skills to contribute to the village of Tempuran Kaloran District Temanggung Regency through the installation of internet networks in order to expand and facilitate access to information by the public. Free internet network installation activities in the framework of Community Service Department of Electrical Engineering Defense Akmil successfully meet the target where there are 30 heads of families who can access the internet for free. Implementation pemasangat internet network implemented for two days, where the first day successfully connect the internet 16 heads of families and the second day connect the internet 16 heads of families . In the installation of the internet there are no obstacles and barriers faced, so that people can easily access the internet for business purposes, learning purposes darring school children and access a variety of social media information.